Advances in databases and information systems : 20th East European Conference, ADBIS 2016, Prague, Czech Republic, August 28-31, 2016. Proceedings /: 20th East European Conference, ADBIS 2016, Prague, Czech Republic, August 28-31, 2016. Proceedings. ([2016]) - Unknown
No abstract available